The Role Of The School Committee In The Management Of Education Management In SMP Negeri 1 Patumbak Deli Serdang - Candra Wijaya; Achmad Bahtiar; Subri Subri (Proceeding International Seminar of Islamic Studies, 2019)
The purpose of this study was to determine the role of school committees in the administration of education in SMP Negeri 1 Patumbak Deli Serdang. And to find out the school committee management in the education management system of SMP Negeri 1 Patumbak Deli Serdang. The research method was carried out with a descriptive qualitative approach with data collection tools using the method of observation, interviews and documentation methods. While the data analysis will be processed so as to obtain a clear understanding of the problems related to the research objectives. And in processing these data, the authors use qualitative data analysis with non-statistical descriptive analytic interactive models.The results of this study are first, that the role of school committees in the administration of education in SMP Negeri 1 Patumbak Deli Serdang is realized in several fields including; as a body of consideration which is divided into three functions, namely the function of giving consideration in the planning of an institution, the implementation of its educational program, and the management of educational resources. Then as a support body that is providing support or support both in terms of funding, information, school needs and others, then as a controlling body, where the role is to control the activities of the school, headmaster, teachers, students and community participation in this matter the guardians students in developing school management in SMP Negeri 1 Patumbak Deli Serdang, and the last role as a liaison body is to become a bridge of relationship between the community and the school related to school information, school needs, student parents' relationships with schools and others.